PHARMACOLOGICALLY ACTIVE α-LINOLENIC ACID (ALA, 18:3ω3), THE PRIMARY PRECURSOR MOLECULE FOR – ω3 SERIES OF POLYUNSATURATED FATTY ACID(PUFA) FROM MANGROVE ECOSYSTEM: Life Science-Zoology - TAPAS KUMAR DAS; SAMANTA, SAMARESH; CHATTERJEE, SUBHASISH; GHOSH, ANITA; KUMAR CHAKRABORTY, SUSANTA (International Journal of Life Science and Pharma Research, 2014)
The fatty acid compositions of the three selected mangrove plant leaves and detritus of the leaves have been studied by gas liquid chromatography and other chromatographic techniques. Altogether 25 components were detected and estimated. Major fatty acids recorded were palmitic (16:0), stearic (18:0), oleic (18:1ω9), linoleic (18:2ω6) and α-linolenic (18:3ω3). Of the unsaturated fatty acids, considerably higher levels of pharmacologically active fatty acids, viz. linoleic and α-linolenic acids were recorded. The α-linolenic acid is incorporated into cell membranes, promotes the health of blood vessels and is converted to long-chain omega-3 fatty acids. Such findings have suggested that these plant species studied are also a potential source of pharmacologically active α-linolenic acid, the primary precursor molecule for – ω3 family of fatty acids in animal tissues.